Vitamin D and Human Health (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Vitamin D research has expanded greatly over the last 10 years, with a more than two-fold increase in annual publications listed in Pubmed with the key word 'vitamin D' from 1675 in 2005 to 3953 in 2014. Part of this increase is due to research showing that vitamin D deficiency is associated with a wide range of diseases and health outcomes. Until the 1980s, the primary focus of vitamin D research (in combination with calcium supplementation) was on bone diseases. Since then, observational studies have linked vitamin D deficiency with increased risk of many diseases: both acute and chronic. This book contains publications on several of these disease groups linked to vitamin D deficiency.